Assessment of knowledge about body postural defects among parents - Klimkiewicz-Wszelaki, Karolina; Sokołowski, Remigiusz; Kasperska, Paulina; Oleksy, Eliza; Ziółkowska, Anna; Stemplowski, Wojciech; Nesteruk, Ewelina; Kwiatkowski, Cyryl; Kędziora-Kornatowska, Kornelia; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Introduction: Postural defects became in recent decades significant problem, both medical and social. Many examinations show that faulty posture affect about 60-80 per cent of children. The rapid development of technology has led to limiting of physical activity which manifests itself by massive occurrence of faulty posture. Therefore it is extremely important to increase the parents knowledge and awareness of the prevention and correction of faulty posture as well as benefit from physical activity. Aim: The aim of the present study was estimation parents knowledge about faulty posture and verification who knows more – parents who have children with correct posture or these who have children with postural defects as well as parents who encourage children to exercise or these who don’t do this. Materials and methods: A survey was conducted in a group of 60 parents. First group: 30 parents of children attending The Postural Defect Clinic, second group: 30 parents of children attending School Complex No. 8 in Bydgoszcz. The original questionnaire was used for the study. Questionnaire to the estimation of parents knowledge consisted of 19 questions: metric questions and knowledge test. The results were analyzed statistically (p<0,05). Results: Parents who enroll children for extra sports are more knowledgeable than parents who do not. Parents whose children have postural problems have no higher knowledge than parents whose children have a correct posture. Parents with higher education have more knowledge about posture defects. Conclusion: Parents knowledge on the prevention and correction of faulty posture is sufficient (mean: 56 per cent correct answers). Nowadays, knowledge should be at a higher level by looking at the frequency of postural defects.